Effects of Implementing a Two-Year Training-Supportive Plan on Acquisition of the Evidence-Based Practice Competency by the Nursing Students - Roghieh Nazari; Fatemeh Hajihosseini; Hamid Sharif Nia; Noushin Mousazadeh; Abdolmotalleb Hasani (Mashhad University of Medical Sciences, 2023)
Background: Teaching evidence-based practice in undergraduate nursing students is limited and requires a complex and step-by-step approach. The aim of this study was exploring the effect of a two-year educational-supportive intervention on undergraduate nursing students, evidence-based practice competency.Method:  This semi-experimental single-group study was conducted in Amol Nursing School from June 2017 to July 2019. Sixty -two undergraduate nursing students who were entered in same academic year, participated in this study as a census.  After assessing the evidence-based practice competency, a two-year educational-supportive intervention was conducted. In the third year, students were taught how to design clinical questions and critique the use of its results in responding. In the fourth year, students performed the above activities under the supervision of faculty members. At the end of the course, the competency level of evidence-based practice was considered as one of the seven test stations, as a post-test.Results: The average age of the students was 20.46±0.92 years and most of them (51.61%) were women. The evidence-based practice competency score of the students before and after the intervention was 13.71±2.31 and 34.71±5.19, respectively, and this difference was statistically significant (P<0.001). Comparison of evidence-based practice competency scores based on gender did not show any statistical difference (P>0.05).Conclusions: The findings showed that the educational-supportive intervention implemented to improve evidence-based practice competence of undergraduate nursing students was effective. Therefore, nursing education practitioners and planners can use this model to nursing education.